Shawāṭāʾ Jazīrat Jarba bayn naswha al-aḥyā ʾ al-mukathaf wa surʿa al-tadhūr al-Khaṭīr lil-muḥīṭ : al-muʿādalla al-mustaḥīl - Bourgou, Mongi (al-Jazira, 1996)
Keywords: Littoraux -- Djerba

Oman and the West : state formation in Oman since 1920 - Owtram, Francis (London School of Economics and Political Science, 1999)
This thesis analyses the external and internal influences on the process of state formation in Oman since 1920 and places this process in comparative perspective with the other states of the Gulf Cooperation Council. It considers the extent to which the concepts of informal empire and collaboration are useful in analysing the relationship between Oman, Britain and the United States. The theoretical framework is the historical materialist paradigm of International Relations. State formation in Oman since 1920 is examined in a historical narrative structured by three themes: (1) the international context of Western involvement, (2) the development of Western strategic interests in Oman and (3) their economic, social and political impact on Oman. The incorporation of the Arabian littoral into the security sphere of the British empire in India separated the Imamate in the mountainous interior of Oman from the British-backed Sultans in Muscat. This culminated in the Treaty of Sib in 1920 following which the government of the Sultanate was restructured by British officials. The discovery of oil in Bahrain in 1932 marked a new phase in the incorporation of the Arabian peninsula into the capitalist world-system. In south-east Arabia this led to the occupation of the interior in 1955 by the British-supported forces of Sa'id bin Taimur. The coup of 1970 in which Qabus became Sultan allowed the development of a pro-Western rentier state and the defeat of the rebels in Dhofar. British imperial withdrawal from the region was completed with the relinquishment of its bases in the Sultanate of Oman in 1977. The development of a strategic relationship between Oman and the United States in the 1980s enhanced American military deployment during the Kuwait crisis of 1990-1991. In the aftermath of this conflict Oman faces the challenge of political development in an environment of diminishing oil reserves.
Keywords: Littoraux -- Djerba

Zone sensible littorale de Ras Remel à Jerba - Scet (Agence de Protection et d’Aménagement du Littoral, 1999)
Keywords: Littoraux -- Djerba

Les sédiments du littoral et leur mobilité : Introduction à l'étude des mécanismes sédimentaires - Le Nindre, Y. M.; Howa, H. (Éditions BRGM, 1999)
Keywords: Littoraux -- Djerba

Milieu littoral et aménagement : le cas du littoral nord oriental de la presqu’île de Zarzis - Bourgou, Mongi (Revue tunisienne de géographie, 1995)
Keywords: Littoraux -- Djerba

Post-Mortem Onshore Transportation of Epiphytic Foraminifera: Recent Example from the Tunisian Coastline - Davaud, Eric; Septfontaine, Michel (Journal of Sedimentary Research, 1995)
The barrier island system that connects Jerba Island to the Tunisian coastline is composed mainly of carbonate bioclastic sands. Well-preserved tests of dead epiphytic foraminifera are abundant on the foreshore and backshore, but they are scattered and poorly preserved on the shoreface, where very fine sand-size eolian quartz, peloids, and broken bioclasts are the main components. The reason for this paradoxical pattern is that most epiphytic foraminifera are very easily removed as suspended load by storm-generated currents and concentrated on beaches, washover fans, and small eolian dunes, kilometers avay from their original life environment. Similar bioaccumulations are common in the fossil record and have often been interpreted incorrectly as prolific biocoenoses.
Keywords: Littoraux -- Djerba

Étude de la gestion de la zone sensible de Ras Remel à Jerba. Résumé du rapport de phase 1 - Apal (SCET-Tunisie, 1999)
Keywords: Littoraux -- Djerba